The Moderating Role of Company Size on Audit Committee Relations and Tax Avoidance - Nora Hilmia Primasari; Siti Mutmainah (Educoretax, 2023)
This research aims to examine the influence of the audit committee on tax avoidance with company size as a moderating variable. The population in this research are mining companies registered in Indonesia for the period 2016 - 2019. This research uses a quantitative approach based on the philosophy of positivism. The data in this research is panel data which was analyzed using the Eviews program, a suitable estimation test is the fixed effect model (FEM). The research results state that the audit committee has a negative effect on tax avoidance.  Company size is able to moderate the relationship between the audit committee and tax avoidance. This is proven by the results which state that company size as a moderating variable can change the direction of the audit committee to have a positive effect on tax avoidance. These results contribute to the Directorate General of Taxes (Direktorat Jenderal Pajak/DJP) being able to pay special attention to large companies that have greater capabilities in designing and implementing tax avoidance strategies, by conducting more in-depth audits and more careful monitoring of tax practices for large companies.